Assessing the gender wage gap: Turkey in the years 2002–2019 - Koral, Zeynep Aktaş; Mercan, Murat Anıl (Economics and Business Review, 2021)
This study investigates the wage differential and discrimination between genders in Turkey based on data taken from the nationally representative Turkish Household Labour Survey for 2002 to 2019. The Blinder–Oaxaca decomposition technique was used which was then integrated into the Heckman’s selection correction procedure. It was found that the gender wage gap is small in the Turkish labour market, while most of this gap originates from the discrimination against women. In addition ignoring the occupational and sectoral effects on the gender wage gap could result in underestimation of the discrimination effects both directly and indirectly through higher human capital of female employees. Lastly all these indicate that the results could likely be specific to the data set.